Knowledge flows, technological change and regional growth in the European Union - Runiewicz-Wardyn, Małgorzata (Contributions to Economics, 2013)
The book provides conceptual and empirical insights into the complex relationship between knowledge flows and regional growth in the EU. The author critically scrutinizes and enhances the RIS (Regional Innovation System) approach, discussing innovation as a technological, institutional and evolutionary process. Moreover, she advances the ongoing discourse on the role of space and technological proximity in the process of innovation and technological externalities. The book closes with an investigation of the role of technological change and knowledge spillovers in the dynamic growth and "catching-up" of EU regions. "Knowledge Flows, Technological Change and Regional Growth in the European Union" focuses on the identification of the elements explaining the linkages between knowledge flows and regional growth. With a critical approach to RIS theory and the need to move to an evolutionary approach to regional innovation systems, the book offers new insights into the complex relationship between space, knowledge and economic growth in the multifaceted European regions. Roberta Capello, Professor of Regional Economics, Politecnico of Milan, Past President of RSAI